Research of stimulating efficiency of blood allogeneic plasma fractions on cell proliferation in vitro conditions - Dzhyvak, V. G.; Dovhalyuk, A. I.; Paliy, I. R.; Klishch, I. M. (Journal of Education, Health and Sport, 2020)
We conducted a comparative experiment on the effect of platelet rich plasma and platelet poor plasma of allogeneic blood of rats on the proliferative activity of different rat cell lines in experimental conditions in vitro. Rat cells such as umbilical cord mesenchymal stem cells, dermal fibroblasts, and fetal myogenic cells were used in the experiment. To compare the proliferative activity of cell lines, the density of the cell population - confluent - was estimated as the percentage of filling the bottom area of the culture vessel with attached and spread cells. As a result of the research it was found that plasma enriched with platelets in the form of 5% supplement to the growth medium has a pronounced stimulating effect on the proliferative activity of fibroblasts, but less effective in the case of cell culture of mesenchymal stem cells. Platelet poor plasma has a physiological effect on the cell cultures of mesenchymal stem cells and rat fibroblasts similar to fetal calf serum. Myogenic rat cells have a high proliferative potential and do not require additional stimulation of platelet rich plasma and platelet poor plasma at the concentrations studied by us.